(untitled) (LIS TODAY, 2025)
This paper has discussed the GROBID as a machine learning tool for extracting bibliographic metadata from PDFs. It provides Ubuntu installation guidance, explains core extraction features, demonstrates applications like metadata and citation analysis, and supports deployment across environments, aiming to help users integrate it into their workflows. Installation on Ubuntu/Debian requires sequentially setting up JDK, Maven, and Git. The GROBID repository, cloned via Git, is built using Gradle and compiled by Maven. Users can configure it as a persistent system service. Customization involves editing the grobid.properties file. Functionality was tested via the web interface using sample PDFs. It effectively transforms unstructured PDFs into structured XML/ TEI, extracting titles, authors, abstracts, and references. It processes standard scholarly PDFs rapidly (2-5 seconds per page) with over 90% accuracy. Its flexibility comes from configurable PDF parsing, citation extraction, and memory management settings. Deployment is simplified via a standalone JAR, and system service setup enables continuous operation in production. The tool is based on open-source machine learning foundation allows deep operational customization, making it exceptional for automated document processing. It operates offline and supports multiple languages, leveraging ML to handle diverse document formats and languages. Its adaptable architecture serves varied domain needs, proving significant for research, library digitization, and enhancing search capabilities.